Central Vowels In The Kru Language Family: Innovation And Areal Spreading - Zogbo, Lynell Marchese (My University, 2019)
While Proto Kru and many languages on both sides of the East-West divide today show a set of 9 oral vowels, a subset of Eastern Kru languages attests a much higher inventory, with up to five distinctive central vowels, resulting in a thirteen vowel +ATR set. The locus for central vowel innovation appears to be in the Godié-Guibéroua region, with neighboring languages at varying stages of innovation. In this paper we attempt to document vocalic inventories, point to developing systems, and speculate on how such innovations occurred, including proximity to resonant liquids (especially in a CV 1 LV 2 environment where V 1 is reduced in various contexts) and to suffixal morpheme boundaries. In some languages, co existing lexical variation (mʊ ∼ mɤ ‘go’, Kagbʊwalɩ dialect of Godié) is one clear pathway to phonological change. Pressure for “rounding out” vocalic systems may also play a role in the unusually high number of innovated central vowels. Interestingly one Western language, Bakwé (Marchese 1989), also has a full set of central vowels, an apparent case of areal spreading. Vydrine’s (2009) hypothesis of a wider cross-family spread of central vowels into southern Mande is also discussed. While this article only scratches the surface of this complicated puzzle, evidence points to intricate interaction between phonological change and areal spreading.
Keywords: Kru language; Central vowels; Innovation